2019
DOI: 10.3390/su11154180
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Standardised Data-Collection Methods in the Improvement of Thermal Comfort Assessment Models for Developing Countries in the Tropics

Abstract: Thermal comfort in the built environment is one of the most defining parameters influencing energy use, environmental quality, and occupant satisfaction. Unfortunately, there is a lack of research in this area within developing countries, which are becoming increasingly urbanised and where mechanical air conditioning demands are rising. Many of these countries are adopting thermal comfort standards such as the ASHRAE Standard 55, the EN 15251, and the ISO 7730 to regulate the use of air-conditioning; even when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…In addition, this tool can also be used in combination with mixed-mode ventilation strategies to reduce energy consumption. This is consistent with studies that concluded that this type of ventilation is an effective way to achieve energy savings in the fight against climate change when considering mild seasons and temperate regions [ 45 , 46 , 47 ]. However, to implement the proposed tool in management systems, the value of the r-squared of the non-linear regression (0.6) should be improved by gathering more data.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, this tool can also be used in combination with mixed-mode ventilation strategies to reduce energy consumption. This is consistent with studies that concluded that this type of ventilation is an effective way to achieve energy savings in the fight against climate change when considering mild seasons and temperate regions [ 45 , 46 , 47 ]. However, to implement the proposed tool in management systems, the value of the r-squared of the non-linear regression (0.6) should be improved by gathering more data.…”
Section: Discussionsupporting
confidence: 91%
“…It is therefore important to develop efficient evaluation procedures, including both measurements and occupant surveys. There are validated survey tools for office environments (https://cbe.berkeley.edu/resources/occupant-survey) [64,65] but analogs are still needed for other commercial building settings [66][67][68]. And mass-produced sensors are being incorporated into monitoring packages that can provide data for sound, temperature, relative humidity, CO2, particulate matter and total VOC with high spatial and temporal resolution [69].…”
Section: Discussionmentioning
confidence: 99%
“…Although these models and standards have been adjusted over time, there is still no academic consensus on their feasibility or applicability within different contexts. Past research by the authors has found that the current mainstream standards are inadequate for the typical cultural, economic and environmental conditions in developing countries with tropical climates, as the information used for their development is based on other regions [12,13]. It is argued that the thermal neutrality resulting from the algorithms suggested by the standards is not necessarily the ideal setting for many occupants [[14], [15], [16]].…”
Section: Methods Detailsmentioning
confidence: 99%